Prevalence of TMD symptoms in Turkish migrants and re-settlers from the former Soviet Union in comparison to a German group. Issue 5 (2nd September 2016) - Diercke, Katja; Zimmermann, Heiko; Hellmann, Daniel; Kim, Ti-Sun; Fricke, Julia; El Sayed, Nihad; Hagenfeld, Daniel; Kühnisch, Jan; Schmitter, Marc; Becher, Heiko
Abstract : Objectives: The objective of this study was to investigate the prevalence of temporomandibular disorder (TMD) symptoms among Turks and re-settlers with German origin from Russia and to compare those findings with a German group from the same area. Method: Sixty-nine Turkish migrants, 50 re-settlers, and 96 Germans were clinically examined according to a short version of the Research Diagnostic Criteria (RDC/TMD) protocol. The subjects participated in a feasibility study of the German National Cohort and were recruited from the study center Heidelberg/Mannheim of the cluster Baden-Württemberg/Saarland. Results: Significant differences emerged between the three ethnic groups for unassisted opening without pain, maximum unassisted opening, and overbite, with highest values for the German group. No significant differences were found for muscle pain on palpation or muscle and joint pain during opening. Discussion: As the authors identified significant differences between the different ethnic groups for metric measurements, it might be beneficial to include questions concerning the ethnicity to the German version of the RDC/TMD for further research, to make the results more comparable.